Analyzing Patient Education Methods to Improve Patient Care in Hospital: A Systematic Review - Ridwan Hasyim, M A; Junadi, P (KnE Life Sciences, 2018)
One way of caring but often unnoticed is through patient education, defined as the process of influencing patient behavior and producing changes in knowledge, attitudes and skills necessary to maintain or improve health. The aim of this systematic review is to analyze various methods of patient education in a way to improve patient care in hospital. This is a systematic review based on PRISMA protocol retrieved from online databases such as ProQuest, JSTOR, Science Direct and Springer Link. Nine journal articles were chosen as eligible library to be reviewed for qualitative synthesis. Six out of nine articles used a qualitative study as the method of delivering patient education, an evaluation in qualitative study is essential for improving patient education. Another two articles used a mixed method study between qualitative and a use of other media and materials. Only one article used observational method, they observed an interpretation check on recording of a tele-patient education. An effective patient education method will have to consider patient and family’s value and norms, which allows adequate interaction between patient and family, and the healthcare providers. As conclusion, an effective communication of patient education must provide knowledge, skills and increased self-awareness. Qualitative method is a great way of delivering patient education, though it would be better if combined with use of other media and materials, such as written materials (e.g., handouts and banner, etc.), telephone counseling, including the Internet. Broadening patient access to and delivering patient education could lead to improved levels of satisfaction. Keywords: patient education to improve patient care, patient education method, patient